Pyridostigmine reduces mortality of patients with severe SARS-CoV-2 infection: A phase 2/3 randomized controlled trial - Sergio Fragoso-Saavedra; Isaac Núñez; Belem M. Audelo-Cruz; Sarahi Arias-Martínez; Daniel Manzur-Sandoval; Alejandro Quintero-Villegas; H. Benjamín García-González; Sergio L. Carbajal-Morelos; Sergio PoncedeLeón-Rosales; José Gotés-Palazuelos; José A. Maza-Larrea; J. Javier Rosales-de la Rosa; et al. (BMC, 2022)
Abstract: Background: Respiratory failure in severe coronavirus disease 2019 (COVID-19) is associated with a severe inflammatory response. Acetylcholine (ACh) reduces systemic inflammation in experimental bacterial and viral infections. Pyridostigmine increases the half-life of endogenous ACh, potentially reducing systemic inflammation. We aimed to determine if pyridostigmine decreases a composite outcome of invasive mechanical ventilation (IMV) and death in adult patients with severe COVID-19. Methods: We performed a double-blinded, placebo-controlled, phase 2/3 randomized controlled trial of oral pyridostigmine (60 mg/day) or placebo as add-on therapy in adult patients admitted due to confirmed severe COVID-19 not requiring IMV at enrollment. The primary outcome was a composite of IMV or death by day 28. Secondary outcomes included reduction of inflammatory markers and circulating cytokines, and 90-day mortality. Adverse events (AEs) related to study treatment were documented and described. Results: We recruited 188 participants (94 per group); 112 (59.6%) were men; the median (IQR) age was 52 (44-64) years. The study was terminated early due to a significant reduction in the primary outcome in the treatment arm and increased difficulty with recruitment. The primary outcome occurred in 22 (23.4%) participants in the placebo group vs. 11 (11.7%) in the pyridostigmine group (hazard ratio, 0.47, 95% confidence interval 0.24-0.9; P = 0.03). This effect was driven by a reduction in mortality (19 vs. 8 deaths, respectively). Conclusion: Our data indicate that adding pyridostigmine to standard care reduces mortality among patients hospitalized for severe COVID-19.